Bionic Functional Structures by Femtosecond Laser Micro/nanofabrication Technologies - Li, Guoqiang (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis combines advanced femtosecond laser micro/nanofabrication technologies and frontier bionic design principles to prepare diverse biomimetic micro/nanostructures to realize their functions. By studying the formation mechanism of the micro/nanostructures, the author identifies various artificial structural colors, three-dimensional micro/nanocage arrays, and fish-scale inspired microcone arrays in different processing environments. Multiple functions such as enhanced antireflection, hydrophobicity, and underwater superoleophobicity are achieved by precisely adjusting laser-machining parameters. This novel design and method have extensive potential applications in the context of new colorizing technologies, microfluidics, microsensors, and biomedicine.